2021
DOI: 10.3390/en14164978
|View full text |Cite
|
Sign up to set email alerts
|

The Review of Carbon Capture-Storage Technologies and Developing Fuel Cells for Enhancing Utilization

Abstract: The amount of CO2 released in the atmosphere has been at a continuous surge in the last decade, and in order to protect the environment from global warming, it is necessary to employ techniques like carbon capture. Developing technologies like Carbon Capture Utilization and Storage aims at mitigating the CO2 content from the air we breathe and has garnered immense research attention. In this review, the authors have aimed to discuss the various technologies that are being used to capture the CO2 from the atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 187 publications
(178 reference statements)
0
25
0
Order By: Relevance
“…The volumetric equation proposed by USDOE [8] for the determination of CO 2 storage for an oil and gas depleted reservoir was altered and used for this project. Equation (4) shows the altered equation utilized for this project.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The volumetric equation proposed by USDOE [8] for the determination of CO 2 storage for an oil and gas depleted reservoir was altered and used for this project. Equation (4) shows the altered equation utilized for this project.…”
Section: Theorymentioning
confidence: 99%
“…In recent decades, global warming as a result of the greenhouse gas effect has become the forefront of every discussion worldwide [1][2][3][4], and it signifies how much this unabated issue is of concern to the inhabitants of the world. To address this issue, this study focuses on the ways in which the greenhouse gas effect can be reduced by capturing, utilizing, and storing anthropogenic CO 2 gas in geologic formations.…”
Section: Introductionmentioning
confidence: 99%
“…Not only in pharmaceutical and medical-based products but also in the production of daily consumer products like soaps, toothpaste, detergents, cosmetic products, etc., noble metal nanoparticles (such as silver, palladium, gold, etc.) have found wide application. , Nanoparticles (NPs) of gold find significant application in medicine as they play important roles in delivery of drugs and diagnosis of various diseases . Furthermore, nanoparticles of silver play an important role in biological-based equilibrium, technology based on sensors, and various other applications related to biomedicine. Nanoparticles of platinum find usage as catalysts, besides being used with other nanoparticles in the field of biomedicine as alloys, shell of core, and other nanostructures that are bimetallic in nature. , In the same way, nanoparticles of palladium play a major role in plasmonic-based wave guiding, sensing, , and electrocatalysis and catalysis. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the role of silica, titania and ZnO NPs for CO 2 capture and found that the inclusion of NPs increases carbon-capturing by at least 8-26% [6][7][8][9]. On the other hand, noticeable increases in oil displacement due to interfacial tension (IFT) modification and wettability alteration have been observed in oil recovery [10,11].…”
Section: Introductionmentioning
confidence: 99%